The state of food security and nutrition in Myanmar 2021-24: Findings from seven rounds of the Myanmar Household Welfare Survey - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
This working paper explores the state of food security and nutrition in Myanmar using seven rounds of nationally representative household panel data collected from December 2021 to July 2024. Overall, the state of food security and nutrition has deteriorated in Myanmar in 2021-24. More than three percent of households were in moderate to severe hunger in April-July 2024. Hunger was highest in Chin (14.4 percent), as well as Rakhine (8.0 percent) and Kayah (5.2 percent) in the latest survey round. Households with a low food consumption score increased from 9.4 percent in December 2021-February 2022 to 17.7 percent in April-June 2023 and remains high at 13.5 percent in April-July 2024. The shares in April-July 2024 were highest in Kayah (52.3 percent), Chin (33.9 percent), and Shan (21.1 percent). Inadequate diet diversity among adults rose from 20.6 percent to 25 percent over December 2021-February 2022 to April-July 2024. Women saw a faster decline in diet quality from December-February 2022 to April-July 2024 (6.3 percentage points increase in poor diet quality vs 2.4 percentage points for men). Decreases in diet quality among adults are driven by lower consumption of nuts and seeds and milk/dairy products. 29.5 percent of all children aged 6-23 months and 20.9 percent of all children aged 6-59 months had inadequate diet quality in the latest round of survey. Regression analysis reveals low income and limited assets to be important risk factors for food security and adequate diet quality. Wage workers and low wage communities are found to be particularly vulnerable. Rising food prices, conflict and physical insecurity increase the likelihood of poor diet quality. Receiving remittances is a source of resilience; remittance-receiving households are less likely to experience hunger or poor dietary diversity at the household, adult, and child level. To avert a full-blown nutrition crisis in Myanmar, effective multisectoral steps are required to protect nutritionally vulnerable populations. Expanded implementation of nutrition- and gender-sensitive social protection programs, including maternal and child cash transfers, particularly to vulnerable groups is called for. Further, given the importance of remittances as an effective coping mechanism, supporting migration and the flow of remittances would help to improve the welfare of the Myanmar population.